The Effect of Oxidative Debris on the Laser Desorption/Ionization Efficiency of Graphene Oxide Derivatives for Mass Spectrometric Analysis of Small Molecules and Synthetic Polymers - Hong, Yu Lim; Seo, Tae Hoon; Jang, Hongje; Kim, Young Kwan (Japan Society for Analytical Chemistry, 2019)
The influence of oxidative debris (OD) on laser desorption/ionization time of flight mass spectrometry (LDI-TOF-MS) analysis using graphene oxide (GO) derivatives was systematically investigated. Specifically, the effects on LDI-TOF-MS analysis of small molecules and synthetic polymers were highlighted. The analytical efficiency of GO was significantly enhanced by removing OD from its surface and the working molecular weight range of GO was considerably extended for analysis of synthetic polymers and small molecules.